A dual‐acidification process for the manufacture of direct‐acidified Cottage cheese. (17th June 2013) - Makhal, Subarna; Kanawjia, Suresh K; Giri, Apurba
<x xml:space="preserve">Abstract</x> A technology is described for manufacturing Cottage cheese which involved initial cold (4 °C) acidification of milk with HCl to bring down the pH to 5.3 followed by tempering slowly to 15 °C and subsequent acidification through slow hydrolysis of glucono delta lactone, resulting in a drop in pH to 5.0 and thereafter renneting at 20 °C followed by setting and cutting of curd and subsequent cooking at 35 °C for ~30 min. The method enabled manufacturing of Cottage cheese curd with average moisture, curd yield and curd hardness being 74.30%, 11.88% and 648.30 mN, respectively.